ANALYSIS OF THERMOTECHNICAL CHARACTERISTICS OF HYDROCARBON FUEL VARIABLE COMPOSITION - E. R. Saifullin; S. A. Nazarychev; A. V. Gazeykina; Y. V. Vankov; I. V. Larionova (Известия высших учебных заведений: Проблемы энергетики)
The content of components in gaseous fuels can vary widely, depending on the source, time and stage of development of a fuel field. The change in composition leads to a change in the thermotechnical characteristics of gas, which affects the efficiency of the combustion process. This article presents the results of calculations of the effect of the composition of fuel on its thermotechnical characteristics. Calculations were carried out using analytical and normative methods. The dependence of the fuel specific heat of combustion on the specific air rate was obtained.